ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN PAJAK PENGHASILAN ORANG PRIBADI (STUDI KASUS KANTOR PELAYANAN PAJAK PRTAMA SEMARANG BARAT) (Students' Journal of Accounting and Banking, 2013)
This study aimed to analyze the effect of the number of taxpayers OP, the amount received SSP and activities extensification taxpayer to total personal income tax receipts, personal income tax revenues contributed greatly in increasing the amount of the government's acceptance of tax advice and infrastructure to meet the needs of a country.The population in this study is the Tax Office Primary West Semarang during 2009 to 2012, the sample was selected using a sensus, with sampling obtained by 48 data’s. And by using linear regression analysis to test the hypothesis. results of the analysis in this study with SPSS tools 19 results showed that the data be processed normally.The results of processing the data, the results of this study indicate that not all hypotheses received. Hypothesis 1 with a variable number of registered WPOP, shows the number of registered WPOP not significant and negative effect on personal income tax revenue, hypothesis 2 with variable SSP received the results showed a significant positive effect on personal income tax revenue, hypothesis 3. with variable extension the taxpayer shows that the results are not significant and negative effect.Keywords: WPOP registered number, the amount received SSP, extensification Taxpayer and personal income tax revenues.